Thyroid disorder in pregnancy and postpartum with neonatal outcome a study in tertiary care centre - Das, Bharati; Khuntia, Puspanjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Thyroid disorders are well known entity in pregnancy. Both mother and baby have to suffer from the consequences. Lot of works has been done and many guidelines too came out over the years but what is actual understanding of the disease process by the mothers about themselves and for their babies especially in developing country like India remained uncovered. This has been analysed in present study. Methods: It is a prospective observational study done in the post-partum programmed department of SCB medical college and hospital, a tertiary care center in eastern part of India for 3 years period. Thyroid dysfunction of the mothers and new born screening of thyroid function of their babies has been assessed. Results: During this period total no of the babies along with their mothers were evaluated were 3762. Total no of thyroid disorders detected in 85 (2.25%) of mothers, among which hypothyroidism in 79 (2.09%) and hyperthyroidism in 6 (0.16%) were found. From total 85 cases, 79 (93%) mothers were hypothyroid and 6 (7%) were hyperthyroid. Among the hypothyroid mothers 32 (40.5%) were diagnosed before present pregnancy and (59.5%) were diagnosed during pregnancy. In the babies of hypothyroid mother, new born screening for thyroid function was done only in 14 (17.7%) cases between 5-10 days. Conclusions: Thyroid screening should be done in pregnancy as universal screening instead of high-risk cases. Documentation and interdepartmental coordination are very much essential in thyroid disorders for further decision by the physician for necessity of continuation of treatment and thyroid function test in the post-partum period for the mothers and its long-term consequences. It also guides the neonatologist or pediatrician doing thyroid function test of their babies. Ideally All newborns should be screened for congenital hypothyroidism as a part of new born screening (NBS) programmed. Effective communication with the mother and the family is very much essential for monitoring and treatment of both mother and the baby.